PRODUCTION OF FEMALE GIANT FRESHWATER PRAWN (Macrobrachium rosenbergii) THROUGH HORMONAL INDUCTION - R.R. Sri Pudji Sinarni Dewi; Ikhsan Khasani; Sularto Sularto; Wahyu Pamungkas (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
The objective of this experiment was to find out the appropriate dosage for producing homogametic female of giant freshwater prawn (Macrobrachium rosenbergii de Man) by feminization. This experiment was carried out at Research Institute for Freshwater Fish Breeding and Aquaculture, Sukamandi. The giant freshwater prawn at PL-5 stage was treated orally by estradiol-17ß. Estradiol-17ß was given orally. The dosage levels are 0, 30, 50, and 70 mg/kg of feed. The hormonal feed was given for 30 days. Prawns were reared in aquaria for 30 days and hapas for 60 days. The parameters observed are sex ratio, survival rate, total length, and body weight. The results showed that estradiol-17ß increased production of female giant freshwater prawn. The best dosage was 70 mg/kg of feed that could produce 65.33% ± 5.64% of female. Survival rate and growth of giant freshwater prawn were not affected by estradiol-17ß (P<0.05).